2016
DOI: 10.1584/jpestics.d15-071
|View full text |Cite
|
Sign up to set email alerts
|

Effect of spray application techniques on spray deposits and residues of bifenthrin in peas under field conditions

Abstract: Five spraying techniques were evaluated for the coverage of bifenthrin on peas under open field conditions. Ultra-low volume sprayer (ULVA) and Ground hydraulic motor with conventional spray gun (GMG) gave number mean diameters (NMDs) from 27 to 68 and from 33 to 73 N/cm 2 with volume mean diameter (VMD) from 50 to 120 and from 320 to 508, respectively. Homogeneity factor values were 2, 2, 2.5, 2.8, and 13.5 in ULVA, Domestic modification of the ground hydraulic motor sprayer with one nozzle (GMO), Ground hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 13 publications
0
11
1
Order By: Relevance
“…Additionally, special legal circumstances in some EU countries, such as Italy, establish a minimum dose of PPP per hectare, independent of canopy characteristics. These legal aspects are contrary to the results of recent studies ( Ferguson et al, 2016;Hanafi et al, 2016;Shen et al, 2017), where it has been demonstrated that an accurate spray adjustment based on canopy characteristics (Gil et al, 2021) allows reducing pesticide quantities while maintaining the efficacy of pest and disease control with a low environmental impact.…”
Section: Introductioncontrasting
confidence: 62%
“…Additionally, special legal circumstances in some EU countries, such as Italy, establish a minimum dose of PPP per hectare, independent of canopy characteristics. These legal aspects are contrary to the results of recent studies ( Ferguson et al, 2016;Hanafi et al, 2016;Shen et al, 2017), where it has been demonstrated that an accurate spray adjustment based on canopy characteristics (Gil et al, 2021) allows reducing pesticide quantities while maintaining the efficacy of pest and disease control with a low environmental impact.…”
Section: Introductioncontrasting
confidence: 62%
“…Pesticide application methods are selected by considering the habits of the target pests, the characteristics of the target site, and the properties of the pesticides [19,20]. The most common pesticide application technics are band spraying, broadcast spraying, drench, foliar, soil injection, space treatment, and spot treatment [19].…”
Section: Pesticide Application Methodsmentioning
confidence: 99%
“…Selecting the right equipment for appropriate pesticide application is important for application efficiency and minimization of the loss of spray solution [132], as well as the reduction of pesticide residuals in the environment and the exposure of and risks to residents and farmers [20,32,133]. Han Li et al [31] discussed the different operating parameters which could obtain a better reference for the determination of field operating parameters, and technical references for field pesticide application and the results of the study indicated that, compared to traditional spraying machinery, unmanned aerial sprayers had advantages of more uniform liquid deposition distribution and better penetration, providing a technical reference for field spray operations and the establishment of a uniform standard for pesticide application technology.…”
Section: The Impact Of Pesticide Application Methods On Exposure and ...mentioning
confidence: 99%
“…Bifenthrin [2-methylbipenyl-3-ylmethyl (z)-(1RS, 3RS)− 3-(chloro-3,3,3-trifluoroprop-1-enyl)−2,2-dimethylcycloro propanecarboxylate] is a third generation synthetic pyrethroids (Choi et al, 2009). The residue studies and dissipation of bifenthrin in several plants and fruits has been studied (Chen et al, 2012;Choi et al, 2009;Hanafi et al, 2016;Katroju et al, 2014;Omirou et al, 2009;Reddy et al, 2014;Tewary et al, 2005). Similarly, pyriproxyfen (4-phenoxyphenyl (RS)−2-(2-pyridyloxy) propyl ether) is a broad spectrum of insect growth regulator that mimics the functioning of juvenile hormone (Devillers, 2020).…”
Section: Introductionmentioning
confidence: 99%